Investigation of iodine in starting, follow-on, special formulae and cereal products for infants - Osterc, Andrej; Stibilj, Vekoslava; Stoś, Katarzyna; Akhal, Tarik (Univerzita Pardubice, 2005)
Newborn babies are entirely dependent on mother's milk and special cases on infant formulae, follow-on formulae and special formulae as the only iodine sources. In the present work we investigated the iodine content in various starting infant formulae, follow-on formulae, special formulae and various other samples intended for preparation of baby food. We compared the values obtained with the declared values where possible, and with data found in the literature with the purpose of examining improvements made during last decade. Radiochemical neutron activation analysis was employed to determine the content of iodine in the selected samples. This method is based on ignition of the irradiated sample in an oxygen atmosphere, followed by absorption of iodine in a reducing acid solution containing 1 M H2SO4 and 10% Na2SO3. Extraction of iodine was achieved with chloroform via the classical redox reaction with 10% NaNO3 and 2.5 M H2SO4. The chemical yield of the procedure for each sample aliquot was determined spectrophotometrically. The values of iodine obtained in eighteen different infant foemulae, with the exception of two, showed insufficient agreement with the declared values and there is still a great need for stricter quality control of infant formulae. The median iodine content of eighteen infant foemulae was 136 ug l-1, implying that newborns would reach the newest recommended daily requirements for iodine when they have consumed approximately 0.5 l of prepared infant formula.
Keywords: jod; Spotřeba; výživa; kojenci; analytické stanovení